(untitled) (Biodiversitas Journal of Biological Diversity, 2017)
Roesma DI, Tjong DH, Munir W, Agesi AV, Chornelia A. 2017. Genetic diversity of Tor douronensis (Pisces: Cyprinidae) in West Sumatra, Indonesia. Biodiversitas 18: 1018-1025. A random amplified polymorphic DNA-polymerase chain reaction (RAPDPCR) analysis was applied to determine the genetic diversity within and among the populations of Tor douronensis in West Sumatra river system. The results provided information for proper breeding, maintenance, and conservation of T. douronensis. The highest and the lowest values of genetic diversity were the population of Batang Matur (H = 0.1571; I = 0.2411) and Batang Malalo (H = 0.0880; I = 0.1353), respectively. The value of genetic differentiation (GST) was 0.4266 while that of heterozygosity between populations (DST) and within a population (HS) was, respectively, 0.088 and 0.1184. The value of gene flow between populations (Nm) was 0.6721. Grouping of individuals in a population based Principal Coordinates Analysis (PCO) and UPGMA was in line with the genetic distance values. Matur and Malalo were the most closely related populations (0.0174) while Batang Gumanti and Batang Sinuruik were the most distantly related populations (0.1918). The genetic variation between populations was lower than the genetic variation within the population of T. douronensis and population of Matur is recommended to be used as brood stock in the procurement of stock.